A temática financeira na agenda da política externa do governo Lula: o BNDES e o modelo de participação e exposição financeira do Brasil na América do Sul - Alves, Rodrigo Maschion (2008)
This work encompasses two different thematic areas: the Brazilian foreign policy studies, area concentrated on the studies of international relations; and the studies with focus on the financial political economy, with special attention to Brazil s public system characterization. Both areas regard a central concern: Brazil s economic development. This research seeks to map two central questions: the articulation between BNDES and PEB for the period from 2003 to 2007; and the Brazil s financial model of participation and exposure in the South-American region defended by this government. This work manages to highlight the importance of financial theme on Brazil s foreign policy agenda during Lula s administration. At the same time, this work understands that the regional financial theme proposed by Lula s government regards a lineage structured in Brazilian financial condition